Predicting Global Takaful Assets - Irwansah; Idris, Muhamad; Prakasa, Muhammad Agung (Islamic Marketing Review, 2024)
The Takaful industry is one of the important pillars of the global Islamic financial system. However, the development of global Takaful assets in recent years shows fluctuating dynamics and tends to slow down. This study aims to predict the development of Global Takaful assets in the coming period using three forecasting methods, namely Trend Analysis (regression over time), Exponential Smoothing with Trend, and Multiplicative Decomposition. The data used is secondary data on Takaful Global's total assets for the period 2012–2017 sourced from the Global Islamic Finance Report (GIFR). The forecasting process is done with the help of QM for Windows software version 3. The results of the study show that all methods resulted in a projected decline in Global Takaful assets in the 2018–2022 period. Based on the Mean Absolute Percentage Error (MAPE) value, the Multiplicative Decomposition method has the highest level of accuracy compared to other methods. These findings indicate the need for a strategy to strengthen the Global Takaful industry, both in terms of regulation, product innovation, and increasing Islamic financial literacy.